Strength and aging resistance of monolithic zirconia: an update to current knowledge - Eleana Kontonasaki; Panagiotis Giasimakopoulos; Athanasios E. Rigos (Elsevier, 2020)
New zirconia compositions with optimized esthetic properties have emerged due to the fast-growing technology in zirconia manufacturing. However, the large variety of commercial products and synthesis routes, make impossible to include all of them under the general term of "monolithic zirconia ceramics". Ultra- or high translucent monolithic formulations contain 3-8 mol% yttria, which results in materials with completely different structure, optical and mechanical properties. The purpose of this study was to provide an update to the current knowledge concerning monolithic zirconia and to review factors related to strength and aging resistance. Factors such as composition, coloring procedures, sintering method and temperature, may affect both strength and aging resistance to a more or less extend. A significant reduction of mechanical properties has been correlated to high translucent zirconia formualtions while regarding aging resistance, the findings are contradictory, necessitating more and thorough investigation. Despite the obvious advantages of contemporary monolithic zirconia ceramics, further scientific evidence is required that will eventually lead to the appropriate laboratory and clinical guidelines for their use. Until then, a safe suggestion should be to utilize high-strength partially-stabilized zirconia for posterior or long span restorations and fully-stabilized ultra-translucent zirconia for anterior single crowns and short span fixed partial dentures.